Shabbir Syndrome: Case Report of a Rare Disease - Meel, Rachna; Wadhwani, Meenakshi (Nepalese Journal of Ophthalmology, 2019)
Purpose: To report a case of Laryngeal Onycho Cutaneous Syndrome in a 10 year old child presenting with an ocular surface mass. Methods: A 10 year old boy presented in the out-patient department with a painless mass in left eye. There was history of airway obstruction requiring tracheotomy in early childhood and recurrent skin ulcerations. Aslit lamp examination revealed fleshy mass arising from the supero-nasalconjunctiva of left eye. Systemic examination revealed ulcerative lesions on cheeks and ears with dystrophic nails in hands and feet. Results: The ocular surface lesion was treated successfully with topical steroid drops. Conclusion: Steroids may be useful in treating early lesion of ocular surface in LOCS. The importance of regular follow must be emphasized for timely management of frequent granulation tissue outgrowth in bid to avoid development of severe symblepharon and blindness.